Deteksi Virus Tungro pada Gulma Padi Sawah Menggunakan Teknik PCR - Ladja, Fausiah T.; Hidayat, Sri Hendrastuti; Damayanti, Tri Asmira; Rauf, Aunu (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Virus tungro disease is a serious problem to rice crop in a certain area of rice production in Indonesia. The disease is caused by a combined infection of Rice Tungro Bacilliform Virus (RTBV) and Rice Tungro Spherical Virus (RTSV). Both viruses were reported to infect ratoon rice plants, weeds, and wild rice. The study was conducted to detect RTBV and RTSV on some weeds. Weed samples were collected from rice fields in West Java, Bali, West Nusa Tenggara, Papua, and West Sumatera. The detection of RTBV and RTSV were carried out using Polymerase Chain Reaction (PCR) and Reverse Transcription (RT) – PCR, employing coat protein gene specific primers. RTBV specific DNA fragment of ~1400 bp size was successfully amplified from various weed species including: F. miliacea, C. iria, M. vaginalis, L. adscendens, S. zeylanica, D. sanguinalis, and E. crusgalli. RTSV specific DNA fragment of ~787 bp size was successfully amplified from weed species of F. miliacea, L. octovalvis, and D. sanguinalis. RTBV or RTSV specific DNA fragment was not amplified from L. flava and P. distichum. Weed samples infected by both viruses did not show any tungro symptom. Virus detection based on molecular technique was able to determine the status of weed whether it is as an alternate host of viruses. Weeds sanitation prior to rice planting, therefore, should be considered as an integral part of virus disease management.